The decline in saving a threat to America's prosperity? - Bosworth, Barry 1942- (Brookings Institution, 2012)
"Examines the decline in saving in the United States over the past quarter-century. Is it a statistical artifact of the official measure of saving? Why don't Americans save? What are the consequences for economic growth, the performance of the aggregate economy, and policy goals?"--Provided by publisher.